Genetic interventions, inequalities and the role of the state - Athanasiadis, Grigorios (Bioethica, 2021)
A central issue in the ethical public debate on genetic enhancement concerns the inequalities in skills, opportunities and welfare that might be created and established between rich and poor. Many argue that if only the wealthy can have access to enhancements, then existing unjust inequalities will be consolidated and new ones will emerge in the future. Therefore, they argue, state has a role to play against the exacerbating of existing inequalities and the emergence of future ones and determine a genetic policy that will regulate a fair distribution of genetic means under specific principles of justice. This article has two main sections. In the first and shorter section, I examine a case where access to enhancement would be unlimited for everyone. In the second and longer section, I examine the principles that a state should adopt in order to treat the unjust inequalities that could result from limited access to enhancement. Finally, I outline part of my own approach to a just genetic state policy.